Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2001
DOI: 10.1115/2001-gt-0303
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Airfoil Clocking in a Three-Stage Low Pressure Turbine

Abstract: A quasi–three–dimensional, blade–to–blade, time–accurate, viscous solver w as used for a three–stage LP turbine study Due to the low Reynolds number, transitional computations were performed. Unsteady analyses were then carried out by varying the circumferential relative position of consecutive vanes and blade rows to study the effects of clocking on the turbine’s performance. A clocking strategy developed in order to limit the number of configurations to be analyzed is discussed. The optimum analytically–dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The numerical results in a three-stage low-pressure turbine of Arnone et al [2] show similar trends as reported by Dorney et al [1]. The effect of full-clocking (clocking of both the rotor and stator blade rows) on the maximal efficiency variation was estimated to be 0.7 per cent.…”
Section: Introductionsupporting
confidence: 79%
“…The numerical results in a three-stage low-pressure turbine of Arnone et al [2] show similar trends as reported by Dorney et al [1]. The effect of full-clocking (clocking of both the rotor and stator blade rows) on the maximal efficiency variation was estimated to be 0.7 per cent.…”
Section: Introductionsupporting
confidence: 79%
“…A number of experimental and numerical studies have been carried out in recent years to investigate these flow phenomena [e.g. Arnone et al 2000Arnone et al , 2002, Eulitz 2000Haldeman et al, 2003;He et al 2002, Howel et al 2001, Huber 1996, Hummel 2002Jouini et al 2003;Reinmoeller et al 2002, Saren et al 2002. The experimental work presented herein is the continuation of our earlier studies, starting from mid-nineties [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Low-pressure turbines behaviour is discussed in detail in [59], where an increase of 0.7% in the efficiency is found by numerical simulations.…”
Section: Cascades Clockingmentioning
confidence: 99%